The Effectiveness of Using Twin Block Functional Appliances and Activators in Class II Malocclusion (Journal of Pharmaceutical Negative Results, 2022)
Background: Malocclusion is a condition of mismatch in occlusion or a mismatch of the opposing teeth when the jaws are in contact. Clinically, it can be manifested in a variety of ways from simple rotation of the teeth, minor diastema to crowding, spacing, protrusion, and some combination. One of the most common malocclusions is class II malocclusion. Class II malocclusion is characterized by retrognathic appearance of the mandible. Class II malocclusions can be treated using several functional appliances such as Twin Blocks and Activators. Objective: To analyze the effectiveness of using twin block functional appliances and activator in class II malocclusion. Method: Data collection was carried out by searching and analyzing literature from the electronic data site Semantic Schoolar, Science Direct and manual search in the publication period 2012 to 2022. Systematic data search using keywords: Twin Block, Activator, Malocclusion, Class II. Conclusion: Both functional appliances, Twin Block and activator, are equally effective in treating patients with Class II malocclusion.The overjet angle, SNB, and ANB increased significantly in both groups.